Breaking the Silence: Exploring Peritraumatic Distress and Negative Emotions in Male and Female Physical Domestic Violence Victims - Pasquale Caponnetto; Vittorio Lenzo; Alberto Sardella; Graziella Chiara Prezzavento; Mirko Casu; Maria C. Quattropani (Health Psychology Research)
# Background